Irrigation Water Supply Patterns in Several Land Uses with Automated Application of Soil Moisture Monitoring Based on Dielectric Technology - Nur Fitriani; Bandi Hermawan; Elsa Lolita Putri; Hasanudin Hasanudin; Hata Dahlan (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
Indonesia is necessary to develop an increase in soil productivity. The decline in soil productivity for agriculture can be caused by several factors, namely land conversion to a decrease in groundwater quantity. The actual pattern of providing irrigation water with the application of dielectric sensor technology is carried out in soil cultivation to create efficiency in providing irrigation water. This research was conducted using a single factor experimental method with repeated measurements on three types of land use, such as land without vegetation, soil with tomato cultivation, and soil with grass. Measurements were carried out using an automated application of soil moisture monitoring based on dielectric technology with two measuring periods. Each measuring period consists of two weeks or fourteen days. Soil sample analysis was carried out at the Bengkulu University soil laboratory. The results of the observations were analyzed using variance (ANOVA) on the 5% F test table, the LSD test was carried out at the 5% level on data that had a significant effect. The results showed that the daily irrigation water for vegetated land was lower than for tomato cultivation and without vegetation in each measurement period. The frequency of irrigation water application in the two observation periods also showed that the land without vegetation had a higher amount and frequency of water application compared to the other two types of land use.